Analisis Pertumbuhan Ekonomi Pengguna Internet, Kemiskinan dan Korupsi di Negara ASEAN: Lower Middle Income - Riska Dewi Putri; Hasdi Aimon (Universitas Negeri Padang, 2022)
This study aims to identify and analyze the response between economic growth, poverty, and corruption in in ASEAN lower middle income countries. Type of this research is descriptive and associative, used a secondary panel data from 2010 to 2017. This research was conducted using the Vector Autoregression (VAR) model through the analysis of Impulse Response Funtion (IRF) and Variance Decomposition (VD) to determine the variability response of a particular variable due to the shock of other variables. The results of this study indicate that: (1) The variability of economic growth is not contributed by the poverty shock in the short term, but in long term the variability of economic growth is contributed by the poverty shock in ASEAN countries:Lower Middle Income. (2) In the short term and long term variability poverty is contributed by the economic growth in ASEAN countries:Lower Middle Income. (3) The variability of poverty is not contibuted by the shock of corruption in the short term, but in the long term the variability of poverty is contributed by the shock of courruption in ASEAN countries:Lower Middle Income. (4) In the short and long term variability curruption is contributed by the shock poverty in ASEAN countries:Lower Middle Income. (5) In the short and long term variability curruption is contributed by the shock economic growth in ASEAN countries:Lower Middle Income. (6) The variability of economic growth is not contributed by the curruption shock in the short term, but in the long term the variability of economic growth is contributed by the curruption shock